NURSE’S EXPERIENCE IN PROVIDING NURSING SERVICES ACCORDING TO COMPETENCE IN INVENTORIES PUBLIC HEALTH IN INPOSITION OF WEST MANGGARAI DISTRICTS- FLORES - Kornelia Fatima Gunsim (Jurnal Ilmiah Perawat Manado (Juiperdo), 2021)
ABSTRAK Kesenjangan antara kompetensi Perawat di Puskesmas Rawat Inap dengan kompetensi yang diharapkan masih perlu dianalisis lebih lanjut. Penelitian ini bertujuan untuk mengeksplorasi pengalaman kompetensi Perawat dalam memberikan pelayanan Keperawatan di Puskesmas Rawat Inap Kabupaten Manggarai Barat dengan desain penelitian desain fenomenologi hermeneutic. Pengambilan data dilakukan selama 2 minggu pada 12 -23 April 2021. Jumlah informan yang terlibat dalam FGDs dan Wawancara semiterstruktur sejumlah 28 perawat pelaksana dan 7 kepala ruang rawat inap. Data penelitian dianalisis menggunakan teknik qualitative content analysis dan cross-case analysis dengan program software nvivo 12 plus. Empat tema yang tereksplorasi terkait kompetensi pengetahuan perawat adalah Proses Keperawatan, Komunikasi, Delegasi, dan Manajer kepala ruang. Ada perbedaan kompetensi pengetahuan dalam proses keperawatan berdasarkan jenjang Pendidikan. Ada perbedaan penilaian persepsi kompetensi pengetahuan berdasarkan posisi informan. Tiga tema yang tereksplorasi terkait kompetensi sikap perawat adalah Keselamatan Pasien, Relasi, dan Tilik Diri. Tiga tema yang tereksplorasi terkait kompetensi keterampilan perawat yaitu Mandiri, Kolaborasi, dan Mentoring. Ada perbedaan kompetensi keterampilan dalam Tindakan berdasarkan jenjang jabatan fungsional. Lima tema yang tereksplorasi terkait faktor motivasi dalam peningkatan kompetensi adalah Jenjang Jabatan, Kepuasan, Kinerja, Kepercayaan dan Pengarahan. Empat Rekomendasi yaitu perlu diadakan pelatihan berkaitan dengan Proses Keperawatan dan Keselamatan Pasien, sosialisasi SOP Penilaian Kinerja dan delegasi. Kata kunci: Kompetensi, Pengetahuan, Keterampilan, sikap dan motivasi ABSTRACT The gap between the competence of nurses in inpatient health centers and the expected competencies still needs to be analyzed further. This study aims to explore the competency experience of nurses in providing nursing Services In Inventories Public Health In Inposition Of West Manggarai Districts Regency with a hermeneutic phenomenological design research design. Data collection was carried out for 2 weeks on 12-23 April 2021. The number of informants involved in FGDs and semi-structured interviews were 28 implementing nurses and 7 heads of inpatient rooms. The research data were analyzed using qualitative content analysis techniques and cross-case analysis with the nvivo 12 plus software program. Four themes that were explored related to nursing knowledge competence were Nursing Process, Communication, Delegation, and Head of Room Manager. There are differences in knowledge competence in the nursing process based on the level of education. There is a difference in the assessment of the perception of knowledge competence based on the position of the informant. Three themes that were explored related to the competence of nurses' attitudes were Patient Safety, Relationships, and Self-Check. Three themes were explored related to the competency of nurses' skills, namely Independent, Collaboration, and Mentoring. There are differences in competency skills in Action based on functional level of position. Five themes that were explored related to motivational factors in increasing competence were Position Level, Satisfaction, Performance, Trust and Direction. Four Recommendations, namely the need for training related to the Nursing Process and Patient Safety, socialization of SOP for Performance Assessment and delegation. Keywords: Competence, Knowledge, Skills, attitude and motivation